KETERBATASAN FOKUS PADA DIMENSI ESKATOLOGIS DALAM MISIOLOGI KONTEMPORER: REFLEKSI 2 KORINTUS 5:18 19 DAN TEORI MINISTRY OF RECONCILIATION - Seprina Karua; Markus Bua'; Liliani Stevani Amba; Yustinus Bunga' (Adisam Publisher, 2026)
This research aims to integrate 2 Corinthians 5:18-19 with the theory of ministry of reconciliation to construct a missiological framework that balances the dimensions of yet and not yet in contemporary mission. Contemporary missiology, particularly the work of Nelus Niemandt, pays great attention to present life through deep contextualization and deep incarnation, but the eschatological dimension and mission as a ministry of reconciliation receive inadequate attention. Method: The research employs a qualitative approach with intertextual exegesis of 2 Corinthians 5:18-19, systematic theological analysis of the theory of ministry of reconciliation, and critical evaluation of Niemandt's missiology. Exegesis demonstrates that reconciliation is God's definitive soteriological action while continuing toward eschatological consummation. The theory of ministry of reconciliation from Schreiter, Volf, and Langmead affirms that reconciliation encompasses vertical, horizontal, and ecological dimensions inseparable from liberation and restorative justice. Niemandt's missiology, though valuable in contextualization, shows limitations in integrating redemptive and eschatological perspectives. Integration produces a holistic missiological framework balancing present transformation with eschatological hope for cosmic renewal as the telos of God's salvific plan.